Effect of early starting low-cost indigenous enteral feeding for pancreatoduodenectomy patients in early post-operative period - Quiyum, Md Abdul; Haque, Razibul; Mostafa, Firoz; Siddique, Omar; Hasan, AZ Mahmudul (Journal of Surgical Sciences, 2021)
Background: Till date most of the time, nutrition after pancreatoduodenectomy (PD) is maintained by parenteral nutrition in the early postoperative period in our setting leading to higher mortality and morbidity. On the other hand, enteral feeding is practiced with commercially formulated costly preparation in rich countries which may not be affordable always in our situation. This study was conducted to see the effect of early enteral formulated feeding from locally available resources. Objective: To established a cost-effective enteral feeding protocol using indigenous food for treating PD patients in our setting. Methodology: Thirty patients who underwent PD in the Department of Hepatobiliary, Pancreatic & Liver Transplant Surgery, BSMMU, Dhaka from January 2020 to December 2020 were included in the study. They were categorized into two groups; Group A(n=15): enteral feeding made with indigenous food and started from POD 2 through nasojejunal tube with additional parenteral support and Group B(n=15): only parenteral nutrition without any enteral feeding continued up to six / seven POD. In all patients, serum albumin, total bilirubin, serum alkaline phosphatase, total count and CRP were measured on POD 1, 3, 7 & 14for assessing nutritional, cholestatic, immunological and inflammatory status. Result: Serum albumin and lymphocyte count were significantly improved following 3rd POD onwards in Group A. The total bilirubin, alkaline phosphatase, total count and CRP were reduced faster in group A, but remained persistently elevated in Group B. In Group A, the morbidity and postoperative hospital stay were found significantly lesser than Group B. Group B had more nutrition related cost than group A. Conclusion: Early starting of enteral feeding prepared from indigenous food is an effective method of maintaining nutrition after PD. It improves the nutrition, immune condition, markedly reduces inflammation and cholestasis after PD and thus it reduces morbidity, post-operative hospital stays and nutrition related cost. Journal of Surgical Sciences (2021) Vol.25(2) : 8-14